Geochemical and mineralogical characterization of Sangiran Mud Vulcano: insights into Rare Earth Element (REE) enrichment - Hapsorol, Cahyo Aji; Budiono, Kharisma Asmarani; Budiono, Kharisma Asmarani; Ibrahim, Alpan; Mariyanto, Mariyanto; Agustine, Eleonora; Indriana, Rina Dwi; Iryanti, Mimin (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Sangiran Mud Volcano (SMV), an inactive mud volcano located in Central Java, Indonesia, exhibits a unique geological framework with promising potential for Rare-Earth Element (REE) mineralization. This study explores the geochemical properties and REE mineral content of SMV through comprehensive analytical methods, including magnetic susceptibility measurements for magnetic property analysis, X-Ray Fluorescence (XRF) for quantitative elemental analysis, X-Ray Diffraction (XRD) X’Pert PRO PANalytical plays a role in identifying the crystalline phases of REE-related minerals, Scanning Electron Microscopy-Energy Dispersive X-Ray Energy Dispersive Spectroscopy (SEM-EDS) Hitachi Flexsem 1000 provides microscopic characterization of morphology and elemental composition, and Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) is used to determine REE concentrations with high precision. The findings showed that SMV samples mostly consist of hematite and cerium, with average concentrations of 83.16% and 16.83%, respectively. Further geochemical analysis identified significant concentrations of REEs, particularly lanthanum (La) and cerium (Ce), with La showing the highest average concentration at 44.39 ppm, followed by Ce at 37.96 ppm. Additionally, XRF analysis showed that the oxide composition in the samples was dominated by SiO2 (55.36%), followed by Fe2 O3 (17.18%), Al2 O3 (11.11%), CaO (15.73%), TiO2 (1.02%), K2 O (0.8%), and ZrO2 (0.048%). XRD analysis showed the highest potential REE content in samples T1 and T7, with silicon iron cerium deuteride concentrations of 19.8% and 19.4%, respectively. SEM-EDS spectra showed that carbon (C) and oxygen (O) are the main elements, while lower concentrations of Al, Si, Fe, K, and Ca were observed, and trace elements, including Mg and Na, were also detected in small amounts, and ICP-OES analysis detected other REEs, including dysprosium (Dy), europium (Eu), gadolinium (Gd), holmium (Ho), neodymium (Nd), praseodymium (Pr), samarium (Sm), terbium (Tb), yttrium (Y), and scandium (Sc). This decision highlights the potential for REE mineralization in the SMV. Further exploration and characterization of this region could enhance understanding of REE enrichment processes in mud volcano systems and have significant implications for future resource development.